2017
DOI: 10.6026/97320630013347
|View full text |Cite
|
Sign up to set email alerts
|

Cholera host response gene networks: preliminary studies

Abstract: Gene network analysis was performed based on published literature describing genes that are possibly interconnected with cholera vaccine responses in vitro in cell culture and in vivo in human patient punch biopsies as well as DNA extracted from blood. These studies produced divergent results. The differences should be replicated and studied further. Included in such studies, patient ethnicities, states of stress, nutrition, and health, as well as the precise characteristics of the various cholera vaccines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Other studies have shown that the proteins neighbor to disease proteins tend to interact with other proteins associated with that disease [74]. Further attempts have also shown that connectivity changes in the protein interaction network from healthy to diseased states can be valuable for predicting novel appropriate drug targets [75,76].…”
Section: Functional Analysis Clustering and Drug Discoverymentioning
confidence: 99%
“…Other studies have shown that the proteins neighbor to disease proteins tend to interact with other proteins associated with that disease [74]. Further attempts have also shown that connectivity changes in the protein interaction network from healthy to diseased states can be valuable for predicting novel appropriate drug targets [75,76].…”
Section: Functional Analysis Clustering and Drug Discoverymentioning
confidence: 99%